Determining a convenient mobile pedometer app and its performance in assessing physical activity status among university students - Mustafa, Norashikin; Muhd Noor, Izzah Atirah; Che Ku Aziz, Che Ku Nur Aishah; Mohd Shukri, Nor Azwani (IIUM Press, 2023)
Introduction: Many young people nowadays have sedentary lifestyle which might contribute to obesity prevalence. With the technology advancement, pedometermobile applications (apps)are now available to promote physical activity and track steps. Nevertheless, not manystudies have systematically evaluated the convenience and reliability of these apps inobjectivelymeasuringphysical activity. Thus, thisstudy aimed to identify the most convenient pedometer app to be used in tracking the number of steps and validate itagainst asubjective assessment (self-reported)method using the International Physical Activity Questionnaire-Short Form(IPAQ-SF)in identifyingphysical activity status among university students.Methods:Undergraduatestudents at the International Islamic University Malaysia aged 18 to 27 years were recruited using convenient sampling. Apreliminary study was conducted among 10 study participants to select between Accupedo® and Map My Walk®pedometer appsfortracking steps count. Theywere required to use both pedometer apps and rate their experience. Subsequently, the selected pedometer app (Accupedo® Pedometer) and the IPAQ were used to assess physical activitystatus of study participants(N=86)over three days (two weekdays and one weekend day).Data obtained bythe pedometer app were categorized as low active, moderateactive and activewhileIPAQ-SF data were categorized intolow, moderate,and highstatus. The relative agreement between these data were analysed using Kappa statistics, cross-classification, and Pearson correlation. Results:It was found that 74% (based on IPAQ) and 91% (based on pedometer app) of the study participants were categorized as low active. The Kappa value was k=0.126 (p=0.016) indicating a slight but significant agreement between these two methods. Cross-classification demonstrated that 40% (n=34) of the study participants were correctly classified into the same tertileswhereas 16% (n=14) were grossly misclassified. In addition, the average steps count/day (by pedometer app) was significantly correlated (r=0.235, p=0.03) with total MET-minutes/week as recorded by the IPAQ-SF. Conclusion:The pedometer app was comparable to the IPAQ-SF in assessingphysical activitystatus. This shows that a cost-free and convenient mobile app is applicable to be used for daily physical activityassessment among young people